Determination of morphologic and immunohistochemical stain (p57 kip2) discrepancy of complete and partial hydatidiform mole by using microsatellite genotyping - Shina Oranratanaphan; Yuthana Khongthip; Wilasinee Areeruk; Surang Triratanachat; Patou Tantbirojn; Vorapong Phupong; Kornkiat Vongpaisarnsin; Ruangsak Lertkhachonsuk (Elsevier, 2020)
Objective: to evaluate the role of microsatellite genotyping in discordant results between morphologic examination and p57Kip2 staining in hydatidiform mole. Materials and methods: 127 cases of hydatidiform mole who had morphologic examination and p57Kip2immunohistochemical staining were evaluated. Six discrepant cases between morphologic examination and p57Kip2 staining were recruited. DNA was extracted from chorionic villi and paired maternal decidual tissue in Formalin fixed paraffin embedded tissue sections. The STR DNA genotyping was performed by Applied Biosystems 3500 Genetic Analyzer. Genetic data analysis was performed by Gene mapper ID-X software. Three concordant cases were used as control. Results were compared to histopathology, p57Kip2 stain and development of post-molar GTN. Results: All controlled cases were confirmed PHM. Two cases of histologic CHM with positive p57Kip2and 2 cases of PHM with negative p57Kip2 were reported as PHM from microsatellite. Other 2 cases of histologic diagnosis PHM with negative p57Kip2 reported as CHM from microsatellite test and both of them developed post-molar GTN. Conclusion: Microsatellite genotyping is a high accuracy method for differential diagnosis from complete and partial hydatidiform moles. However, cost of microsatellite genotyping is still too high to use routinely. Therefore, selected use in discrepancy cases may be suitable.